Effect of permeation enhancers on the penetration mechanism of transfersomal gel of ketoconazole - Reshmy Rajan; Deepa T Vasudevan (Wolters Kluwer Medknow Publications, 2012)
The aim of the present research work was to investigate the potential of transfersome formulations for transdermal delivery of Ketoconazole (KTZ). KTZ is a broad-spectrum antifungal agent that is active against a wide variety of fungi and yeasts. It is readily but incompletely absorbed after oral dosing and is highly variable. The transfersomes were formulated by lipid film hydration technique using Rotary vacuum Evaporator. The prepared transfersomes were converted into suitable gel formulation and is evaluated for their gel characteristics like pH, viscosity, spreadability, extrudability, homogeneity, drug content, etc. Suitable essential oils acting as natural permeation enhancers were added to the transfersomal formulation of KTZ for their release studies. Studies proved that addition of suitable permeation enhancers to the transfersomal formulation improved the release and permeation of KTZ, which showed that the permeation enhancers modify the barrier to penetration present in skin without itself undergoing any change. From the various essential oils which are used as permeation enhancers, the formulation containing Eucalyptus oil showed better in vitro release and permeation as compared with other formulations containing different permeation enhancers.